Dating of Holocene fluvial deposits in the southern Sierras Pampeanas (Argentina) by matching paleomagnetic secular variation to a geomagnetic field model. (March 2021) - Gogorza, C.S.G.; Irurzun, M.A.; Heider, G.; Goguitchaichvili, A.; Ojeda, G.; Chiesa, J.; Greco, C.
Abstract: A 2-m long Holocene sedimentary sequence collected from a fluvial system located in the eastern piedmont of Sierra de Las Quijadas (San Luis, Argentina) was dated by comparing its paleomagnetic secular variation (PSV) record with the SHA.DIF.14 k time-varying spherical harmonic geomagnetic field model. Rock magnetic data suggest that the magnetic signal is mainly carried by low-coercivity magnetic minerals like magnetite. Low field magnetic susceptibility, used as a magnetic concentration parameter, shows a variation of about a factor of two along the profile. Progressive demagnetization experiments of the natural remanent magnetization show the presence of a stable magnetic component, and the Characteristic Remanent Magnetization directions are well defined (MAD <5°). The obtained magnetic inclination, declination, and the relative paleointensity (RPI) records were then compared with previously published lacustrine Holocene records from Argentina. Several common features and similar millennial-scale fluctuations are observed among the records, supporting a common geomagnetic origin. The consistency and good match among natural archives on a broader scale in different Argentinian regions suggest that the PSV records of El Chimborazo site are reliable and can thus be used to better constrain the secular variation path of the geomagnetic field in this area. Highlights: A detailed paleomagnetic study was performed on a Holocene sedimentary sequence in San Luis Province, Argentina. This study confirms the potential use of paleomagnetic secular variation computed by SHA.DIF.14 k as a dating tool for records from Argentina. The results encourage us to perform further work in this region, where there is lack of paleomagnetic information.